2019
DOI: 10.3390/su11216142
|View full text |Cite
|
Sign up to set email alerts
|

Study on Shear Strength of Xanthan Gum-Amended Soil

Abstract: When construction work is planned on soil with inadequate shear strength, its engineering properties need to be improved. Chemical stabilization is one of the solutions for soil strength improvement. Currently, the most common additive that is used for chemical soil improvement is cement. Cement is an effective solution, but it has several negative effects on the environment. Therefore, the urges for environment-friendly solutions that can replace cement and show good potential for sustainable engineering are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…These findings are consistent with previous research studies of biopolymer-treated soil under triaxial loading conditions showing that biopolymers can increase the peak deviatoric stress 40,[42][43][44][45][46] . On the other hand, Karimi 47 showed that the maximum deviatoric stress of 1% XG-treated silt can decrease in the period between five and 30 days.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previous research studies of biopolymer-treated soil under triaxial loading conditions showing that biopolymers can increase the peak deviatoric stress 40,[42][43][44][45][46] . On the other hand, Karimi 47 showed that the maximum deviatoric stress of 1% XG-treated silt can decrease in the period between five and 30 days.…”
Section: Resultssupporting
confidence: 93%
“…Fig. 11a shows the interaction of an XG biopolymer and pure sand from the author's previous studies 46 . The formation of XG can clearly be seen as a coating agent surrounding coarse-grained particles and bridging the particles that are not in direct contact.…”
Section: Direct Shear Testmentioning
confidence: 99%
“…This was due to an increase in the interfacial cohesion. This may be due to the formation of a biofilm between the clay particles and the geotextile surface which caused them to adhere together more tightly [55,56]. The enhanced interfacial shear strengths of the treated samples were due to the increased interfacial cohesions and interfacial friction angles.…”
Section: The Interfacial Direct Shear Testsmentioning
confidence: 99%
“…A summary of recent studies on biopolymer-treated soil is presented in Table 2. Biopolymer content [116][117][118] Dehydration time [116][117][118][119] Durability [117,119] Direct Shear Dehydration time [117,119] Splitting Tensile Biopolymer content [117] Compaction Biopolymer content [116] Consistency limits Biopolymer content [116] Permeability Dehydration time [119] Sand Unconfined compressive strength…”
Section: Biopolymer-clay Interactionmentioning
confidence: 99%